PHENOMENOLOGICAL QUALITATIVE STUDY OF THE FIRST EXPERIENCE OF BRIMOB TROOPS THE FIRING SQUAD EXECUTORS - Ramadiany, Nungky; Sakti, Hastaning (Airlangga Development Journal, 2024)
The aim of this study is to figure out on the first experience of Brimob troops as an executor of firing squad in Nusakambangan. The approach used in this study is qualitative with phenomenological method and the data analysis technique using Individual Phenomonenology Description (DFI). The subjects involved in this study are three Brimob troops who had been selected as an executor of firing squad using a purposive method. The method of collecting data is semi-structured interviews. The result of this study is that two subjects experienced a conflict when they were ordered to become the executor. The subjects were ready to carry out that order, but they thought of the sin of killing a people who have no resistance. Therefore, there were doubts to carry out that order. A spiritual guidance from kyai who came from Brimob was able to overcome the doubts and become the reinforcement to be sure to carry out their duty that night. Three subjects experienced anxiety before firing on the form of worrying about making mistake, so the subjects regulated their emotions. Entering the firing range, the subjects focused on the implementation so that they dared to shoot the convicted person. The impact of the execution made two subjects experience flashbacks by carrying out the execution and then they overcome them by letting the memories flow. Therefore, they could forget themselves as time went on and the activities at Brimob. Keyword: Brimob Troops, Death Penalty, Executor of Firing Squad, Phenomenological Qualitative Study